Comparison of faecal bile acid profiles between patients with adenomatous polyps of the large bowel and healthy subjects in Japan. Issue 8 (August 1984) - Tanida, N; Hikasa, Y; Shimoyama, T; Setchell, K D
Abstract : Faecal bile acid excretion was examined in 13 patients with adenomatous polyps of the large bowel and compared with a series of matched healthy subjects. Bile acids were analysed in detail with respect to the composition of individual bile acids and their mode of conjugation. The total excretion of bile acids by the patient group and the healthy subjects ranged from 55.0-837.6 mumol/day (median 233.8, mean 346.9) and 93.8-712.3 mumol/day (median 489.2, mean 386.7) respectively. Expressed as mumol/g faecal weight these values were 0.6-4.8 (median 2.2, mean 2.4) and 0.4-5.8 (median 2.2, mean 2.8) and in terms of mumol/g faecal dry weight, 1.9-50.7 (median 10.1, mean 16.5) and 3.9-32.4 (median 16.3, mean 16.7) respectively for the two groups. The composition of the individual bile acids and their distribution within the various conjugate fractions was essentially the same for both groups. Cholenoic acid (5 beta-chol-3-enoic acid), an unusual bile acid, was detected in one patient and three healthy subjects. These results revealed no significant quantitative differences in bile acid excretion between the group of patients with adenomatous polyps and those of healthy subjects.